Hyperhomocysteinemia in recurrent pregnancy loss and the effect of folic acid and vitamin B12 on homocysteine levels: a prospective analysis - Mukhopadhyay, Indrani; Pruthviraj, V.; S., Rao P.; Biswas, Manash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Recurrent pregnancy loss (RPL) affects about 5% of women. High levels of homocysteine, termed hyperhomocysteinemia, have been implicated in a number of pathologic processes in the venous and arterial vascular systems. Hyperhomocysteinemia in pregnant women has been associated with deep venous thrombosis, recurrent miscarriage, abruption placentae, preeclampsia, neural tube defects, and fetal growth restriction. This study aims at determining association between hyperhomocysteinemia and recurrent pregnancy loss and also association of folic acid (vitamin B 9) and vitamin B 12 with hyperhomocysteinemia (HHCY), in reducing its levels in the body and thus preventing obstetric complications. Methods: A prospective study of pregnant mothers booked at our hospital over a period of two years with history of unexplained RPL were included in the study and their serum homocysteine levels were assessed. Hyperhomocysteinemia (>12 micromol/l) patients were treated with folic acid and vitamin B12 supplements and homocysteine levels were assessed again, post treatment. Results: Out of the 100 patients who were assessed, 32% of RPL patients had hyperhomocysteinemia. Folic acid and VitB12 supplementation reduced homocysteine levels and this was found to be statistically significant. Conclusions: Hyperhomocysteinemia is associated with RPL. Vitamin supplementation to those with hyperhomocysteinemia, decreases homocysteine levels.